Autoimmune Atrophic Gastritis: The Role of miRNA in Relation to Helicobacter Pylori Infection - Zingone, Fabiana; Pilotto, Valentina; Cardin, Romilda; Maddalo, Gemma; Orlando, Costanza; Fassan, Matteo; Marsilio, Ilaria; Collesei, Eugenio; Pelizzaro, Filippo; Farinati, Fabio (Frontiers in Immunology, 2022)
Introduction MicroRNAs (miRNAs) have been proposed as diagnostic markers, biomarkers of neoplastic progression, and possible therapeutic targets in several immune-mediated diseases. We aimed to analyze the expression profile of selected miRNAs (miR21, miR142, miR223, miR155) in patients with autoimmune atrophic gastritis (AAG), patients with non-autoimmune multifocal atrophic gastritis (MAG), and healthy control subjects (HC). Materials and methods A total of 103 patients with AAG were consecutively recruited for this study among those attending our gastroenterology outpatient clinic. Participating patients were divided into two groups: primary, not Helicobacter pylori (HP)-associated related AAG (n=57, P-AAG) and HP-associated AAG (n=46, HP-AAG); this subgroup included HP-positive patients, patients with previously reported HP infection, and patients harboring antral atrophy, considered as a stigma of HP infection. We also included 20 sex-age-matched MAG patients and 10 HC. Upper endoscopy with gastric biopsies were performed on each AAG and MAG patient. Circulating levels of miR21-5p, miR142-3p, miR223-3p, and miR155-5p were measured by RT-PCR in all groups. Results MiR-21 was over-expressed in P-AAG (p=0.02), HP-AAG (p = 0.04), and MAG (p=0.03) compared with HC. By contrast, miR-142 was more expressed in HC than in HP-AAG (p=0.04) and MAG (p=0.03). MiR-155 showed no significant differences among the four subgroups, while, unexpectedly, miR-223 was overexpressed in HC compared to P-AAG (p=0.01), HP-AAG (p=0.003), and MAG (p<0.001), and was higher in P-AAG than in MAG (p=0.05). Conclusions MiR-21 was over-expressed in patients with gastric precancerous conditions irrespective of etiology, while in the same subgroups miR-142 and miR-223 were under-expressed compared to healthy controls. Controlling miRNAs up- or downregulation could lead to a breakthrough in treating chronic autoimmune diseases and potentially interfere with the progression to cancer.